Estratégias de marketing digital para supermercados. - CISNE, Matheus; OLIVEIRA, Luis Henrique de (275, 2025)
Este trabalho analisa as principais estratégias de marketing digital utilizadas por redes supermercadistas, destacando sua importância para o fortalecimento da marca, delização de clientes e aumento das vendas. A pesquisa, de caráter qualitativo e exploratório, baseia- se em revisão bibliográca e análise de práticas do setor. Conclui-se que o uso integrado de ferramentas digitais, como redes sociais, e- commerce e programas de delidade, é essencial para o crescimento e competitividade dos supermercados na era digital.

This study analyzes the main digital marketing strategies used by supermarket chains, emphasizing their importance for brand strengthening, customer loyalty, and sales growth. The qualitative and exploratory research is based on a bibliographical review and sector practices analysis. It concludes that the integrated use of digital tools such as social media, e- commerce, and loyalty programs is essential for supermarket competitiveness in the digital era.This study analyzes the main digital marketing strategies used by supermarket chains, emphasizing their importance for brand strengthening, customer loyalty, and sales growth. The qualitative and exploratory research is based on a bibliographical review and sector practices analysis. It concludes that the integrated use of digital tools such as social media, e-commerce, and loyalty programs is essential for supermarket competitiveness in the digital era.
Digital marketing strategies for supermarkets.
Trabalho de conclusão de curso. Artigo
Keywords: Marketing; Supermercado; Gestão e Negócios